Who seeks public treatment for substance abuse in Brazil? Results of a multicenter study involving four Brazilian state capitals - Faller,Sibele (2014)
OBJECTIVE: To assess the characteristics of alcohol and drug users who seek treatment at the Brazilian Unified Health System in Brazil.METHOD:A multicenter cross-sectional study involving five clinical and research centers located in four Brazilian state capitals was conducted with 740 in- and outpatients. The only exclusion criterion was the presence of neurological or severe psychiatric symptoms at the moment of the interview. The Addiction Severity Index (ASI-6) and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) were used to assess the severity of substance use and the problems related.RESULTS: There were significantly more men than women in the sample; mean age was 36 years. The drug most frequently used at all sites was alcohol (78%), followed by cocaine/crack (51%). Alcohol was the drug that most commonly motivated treatment seeking, at all centers. ASI-6 Summary Scores for Recent Functioning (SS-Rs) were quite similar among centers. SS-Rs were compared between users who had never received treatment for psychoactive substance abuse (n = 265, 36.1%) and those who had already been treated at one or more occasions (n = 470, 63.9%). This analysis revealed significant differences between the groups in the drug, psychiatric symptoms, legal, and family/social problems areas (p < 0.05).CONCLUSION: Our findings confirm previous evidence suggesting that the management of patients seeking drug abuse treatment should take several different aspects into consideration, e.g., education, employment, and family relationships, which often appear as areas of concern for these individuals.